Influential knowledge management factors in the acceptance of mobile learning among university students - Duche-Pérez, Aleixandre Brian; Grundy-López, Ricardo Enrique; Hillpa-Zuñiga, Manuel Edmundo; Escobar-Juárez, Antonio Miguel; Aguilar-Gonzales, Hugo Efraín (International Journal of Innovative Research and Scientific Studies, 2025)
The accelerated integration of mobile technologies in higher education has fostered the adoption of Mobile Learning (M-learning) as a flexible, accessible, and student-centered pedagogical model. However, the successful acceptance and sustained use of these platforms require the interplay of various factors. This study aims to examine the influence of key knowledge management processes—specifically, knowledge application, sharing, and protection—along with constructs from the Technology Acceptance Model (TAM), on M-learning acceptance among university students. A quantitative, cross-sectional research design was employed, involving 150 undergraduate students from a private university in Peru. Data were collected using a validated polychoric Likert-scale questionnaire and analyzed through Partial Least Squares Structural Equation Modeling (PLS-SEM). Results indicate that perceived ease of use, perceived usefulness, and knowledge sharing positively affect the application of knowledge within M-learning environments, confirming the relevance of integrating knowledge management principles with TAM. Notably, the relationship between knowledge application and actual system use, as well as between behavioral intention and knowledge application, was not statistically significant, suggesting the presence of unmeasured contextual factors. The model demonstrated strong explanatory power for knowledge application (R² = 0.739), while the explanatory power for actual system use was moderate (R² = 0.243). Findings underscore the need for educational institutions to design user-friendly M-learning platforms, promote collaborative knowledge exchange, and consider institutional and motivational variables that may enhance the sustained adoption of mobile learning technologies.